2022
DOI: 10.3390/jcm11133794
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Incidence of Neuroendocrine Neoplasms Worldwide: Current Knowledge and Open Issues

Abstract: Neuroendocrine neoplasms (NENs) include a heterogeneous group of tumors derived from neuroendocrine cells, most commonly arising from the gastro-entero-pancreatic (GEP) and bronchopulmonary tracts [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…Continuously increasing ASIR of GEP-NEN over the last decades were reported worldwide. [4][5][6]16,18,22 NEN incidence rates varied according to gender and ethnicity, geographic region, and tumor site. 1,6,22 Few studies investigated NEN in Germany 29 focusing either on NETs in general or on one selected GEP site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuously increasing ASIR of GEP-NEN over the last decades were reported worldwide. [4][5][6]16,18,22 NEN incidence rates varied according to gender and ethnicity, geographic region, and tumor site. 1,6,22 Few studies investigated NEN in Germany 29 focusing either on NETs in general or on one selected GEP site.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond other, these consisted of a change in consent on malignancy of specific histologic codes ('behavior code' change) and the inclusion of new histologic codes, for example, the functioning pancreatic neuroendocrine tumors (PanNETs), finally implemented in the first revision of the International Classification of Diseases for Oncology (ICD-O3). 14 Previous epidemiological research on GEP-NEN reported continuously rising incidence rates for the last decades, 6,[15][16][17][18] predominantly for countries of Western Europe, North America, and from Japan. The United States, to give just one example, experienced a strong increase of GEP-NEN rates, which rose 3.6-fold between 1973 and 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall incidence of NENs has continued to increase over the past 40 years, and the incidence of pNETs has also increased ( 8 10 ). pNETs are heterogeneous tumors of the neuroendocrine system originating from islet cells of the pancreas ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…pNENs are rare pancreatic tumors, the incidence of which has increased significantly in recent years. With the advancement of inspection technology and the popularization of health examinations, the clinical detection rate of pNENs has also shown an upward trend ( 7 , 8 ). More than half of the pNENs are G1 pancreatic NETs (G1 pNETs).…”
Section: Introductionmentioning
confidence: 99%